Occupational studies on the exposure to diisocyanates and e-waste. Collection of biological samples for E-waste study (blood, urine, hair, buccal cells) - Silva, Maria João (2021)
E-waste study (blood, urine, hair, buccal cells): biological samples collection - Overview and objectives: Harmonization of the general procedure for human specimens collection, storage and transfer in order to guarantee samples traceability, quality of the analytical data and ensure that ethical and safety recommendations are followed.